Pengaruh Marketing Mix, Harga Dan Customer Experience Terhadap Kepuasan Pelanggan Pada Pasar Banyuasri Singaraja - Ni Putu Pebri Prasanthi; Ni Wayan Novi Budiasni (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine the impact of the marketing mix, price and customer experience on customer satisfaction at the Banyuasri Singaraja Market. The examination procedure used in this research is validity and reliability test, classical assumption test, multiple linear regression analysis, t-test, analysis of determination and f-test test. The results of the review show that the promotion mix affects customer satisfaction at the Banyuasri Singaraja Market. From the test results with the T test, it shows that the marketing mix has a significant effect on customer satisfaction. Price affects customer satisfaction at Banyuasri Singaraja Market. From the test results with the T test shows that the price affects customer satisfaction. Customer experience is related to customer satisfaction at the Banyuasri Singaraja Market. From the test results with the T test shows that customer experience affects customer satisfaction. Judging from the f-test, it is found that the F-count > F-table is 212.297 > 3.12, this indicates that the marketing mix, price and customer experience basically affect customer satisfaction with a sig level. big. 0.000 < 0.050. Keywords : Marketing Mix, Price, Customer Experience, Customer Satisfaction